Review of upper extremity bone metastasis: A retrospective cohort study of 61 patients - Başdelioğlu, Koray (Journal of Surgery and Medicine, 2020)
Aim: Although bone metastasis is the most common bone cancer in adults, its spread to the upper extremity is relatively low. Distribution characteristics of upper extremity bone metastases are not clearly defined. In this study, we aimed to investigate upper extremity metastases, reveal the distribution of upper extremity metastases compared to primary cancers, and evaluate their relationship with additional bone metastases and additional visceral organ metastases. Methods: Sixty-one patients diagnosed with upper extremity metastasis between 2018-2020 were included in the study and analyzed retrospectively. Clinical data, pathology, PET-CT and MRI reports were evaluated. Demographic characteristics (age, gender), primary cancer type, metastasis location (scapula, clavicle, humerus (proximal, diaphysis, distal) and forearm (proximal, diaphysis and distal)), number of metastases (single / multiple foci), additional bone and visceral organ metastases were evaluated. Results: Thirteen (52.00%) female and 22 (61.11%) male patients had multiple upper extremity metastases (P=0.657). The most common location of metastasis was proximal humerus for both genders. Proximal humerus was the most common metastasis location in breast (58.82%), lung (55.56%) and prostate (87.50%) cancers. Scapula was the most common metastasis location in gastrointestinal (87.50%) and urinary tract (83.33%) cancers. Scapula and proximal humerus were the most common metastasis locations in gynecologic (66.67%) cancers. The most common accompanying bone metastasis site was the vertebra for both genders. The most common visceral organ metastasis was the lung (20.00%) in females and liver (16.67%) in males. Conclusion: The most common location of metastases in the upper extremity is the proximal humerus, followed by the scapula. The incidence of upper extremity metastasis decreases from proximal to distal. Solving this mechanism may be beneficial for treatment and survival.